Myocardial blood volume and the amount of viable myocardium early after mechanical reperfusion of acute myocardial infarction: prospective study using venous contrast echocardiography. Issue 4 (1st April 2002) - Andrássy, P; Zielinska, M; Busch, R; Schömig, A; Firschke, C
Abstract : Background: Myocardial capillary perfusion is a prerequisite of myocellular viability after reperfusion of acute myocardial infarction. It was hypothesised that the magnitude of myocardial capillary perfusion, assessed by transmural signal intensity in venous contrast echocardiography as a corollary of the blood volume of myocardial capillaries, and the amount of viable myocardium, represented by differential levels of contractile function two weeks after reperfusion, are correlated. Objectives: To evaluate the role of venous contrast echocardiography for the identification of viable myocardium in patients with acute myocardial infarction early after successful mechanical reperfusion. Methods: 60 patients with a first acute myocardial infarction underwent venous contrast echocardiography several hours after successful mechanical reperfusion (median time interval 190 min.). The relative transmural videointensity (median (25th, 75th percentiles)) of akinetic segments was determined. After two weeks, contractile function was re-evaluated at rest and during dobutamine infusion if segments without functional recovery were present. Results: Relative videointensity early after reperfusion differed significantly between functional groups after two weeks: normokinesia (88% (77%, 100%)), hypokinesia (74% (54%, 99%)), and akinesia with (61% (48%, 76%)) and without contractile reserve (31% (22%, 46%)). Relative videointensity and contractile function were significantly correlated ( r = −0.67). The diagnostic accuracy of relative videointensity > 50% for prediction of contractility of initially akinetic segments at rest or during dobutamine was 82% (χ 2 = 76.2, p < 0.001). Conclusions: Early after successful mechanical reperfusion of acute myocardial infarction, the magnitude of capillary perfusion in the perfusion territory of an infarct related artery is correlated with the amount of viable myocardium. Quantitative venous contrast echocardiography can be used for accurate identification of viable myocardium.